Indigenous Trees-based Agroforestry Systems Course Module - Assogbadjo, Achille Ephrem; Avakoudjo, Hospice G. Gracias; Egeru, Anthony; Salako, Kolawolé Valère (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
At the end of the course module, participants will acquire a comprehensive set of competences to effectively engage in Indigenous tree-based agroforestry systems. They will gain a deep understanding of the central role indigenous trees play in agroforestry systems, particularly in enhancing resilience and facilitating community adaptation to climate change. This knowledge will enable trainees to articulate the significance of indigenous trees in sustainable land management practices. Additionally, participants will develop robust planning skills essential for the successful adoption of agroforestry practices, including the identification and removal of constraints hindering implementation.